Jumlah Keragaman Gender, dan Kebangsaan Dewan Direksi sebagai Determinan Kinerja Perusahaan - Andrianov Andrianov; Awan Santosa (Departement of Mathematics Education, 2023)
This study aims to analyze the effect of the number of boards of directors on company performance, analyze the effect of board gender diversity on company performance, analyze the effect of board nationality on company performance, and analyze the effect of the number of boards of directors, board gender diversity, and board nationality together on company performance. The samples in this study are six banks whose shares are mostly owned by foreigners. The data in this study were obtained from the annual reports of the sample banks for the period 2016-2022. Data analysis in this study used classical assumption tests and panel regression. The results of data analysis show that the number of boards of directors has a significant positive effect on company performance, gender diversity of the board of directors has a significant negative effect on company performance, nationality of the board of directors has no significant effect on company performance, the number of boards of directors, gender diversity of the board of directors, and nationality of the board of directors together have a significant effect on company performance. The findings of this study have implications for academics and investors.